3D‐Printed haptic "Reverse" models for preoperative planning in soft tissue reconstruction: A case report. Issue 2 (21st July 2014) - Chae, Michael P.; Lin, Frank; Spychal, Robert T.; Hunter‐Smith, David J.; Rozen, Warren Matthew
<x xml:space="preserve">Abstract</x> In reconstructive surgery, preoperative planning is essential for optimal functional and aesthetic outcome. Creating a three‐dimensional (3D) model from two‐dimensional (2D) imaging data by rapid prototyping has been used in industrial design for decades but has only recently been introduced for medical application. 3D printing is one such technique that is fast, convenient, and relatively affordable. In this report, we present a case in which a reproducible method for producing a 3D‐printed "reverse model" representing a skin wound defect was used for flap design and harvesting. This comprised a 82‐year‐old man with an exposed ankle prosthesis after serial soft tissue debridements for wound infection. Soft tissue coverage and dead‐space filling were planned with a composite radial forearm free flap (RFFF). Computed tomographic angiography (CTA) of the donor site (left forearm), recipient site (right ankle), and the left ankle was performed. 2D data from the CTA was 3D‐reconstructed using computer software, with a 3D image of the left ankle used as a "control." A 3D model was created by superimposing the left and right ankle images, to create a "reverse image" of the defect, and printed using a 3D printer. The RFFF was thus planned and executed effectively, without complication. To our knowledge, this is the first report of a mechanism of calculating a soft tissue wound defect and producing a 3D model that may be useful for surgical planning. 3D printing and particularly "reverse" modeling may be versatile options in reconstructive planning, and have the potential for broad application. © 2014 Wiley Periodicals, Inc. Microsurgery 35:148–153, 2015.